Applied positive school psychology - Giraldez, Andrea; Burke, Jolanta (Routledge, Taylor & Francis Group, 2023)
"Applied Positive School Psychology is an essential guide to help teachers regain their own and assist the school community in rebuilding their health post-pandemic. While research in positive psychology is thriving, teachers and educational practitioners find it challenging to apply it in their daily practice. This practical book fills the gap between theory and practice and provides practitioners with an evidence-based toolkit on using the positive psychology in their school communities. With contributions from experts in their field, this important resource explores student wellbeing, teacher wellbeing, inclusion, developing positive relationships, creativity, and therapeutic art. Written with the practitioner in mind, Applied Positive School Psychology is a must read for the teaching community and those interested in positive education. It will also be of interest to academics specialising in wellbeing or education, educational psychologists, and education policy makers"--